2023
DOI: 10.3389/fonc.2023.1199105
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia: syndicating triple negative breast cancer against various therapeutic regimens

Abstract: Triple-negative breast cancer (TNBC) is one of the deadliest subtypes of breast cancer (BC) for its high aggressiveness, heterogeneity, and hypoxic nature. Based on biological and clinical observations the TNBC related mortality is very high worldwide. Emerging studies have clearly demonstrated that hypoxia regulates the critical metabolic, developmental, and survival pathways in TNBC, which include glycolysis and angiogenesis. Alterations to these pathways accelerate the cancer stem cells (CSCs) enrichment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 347 publications
(363 reference statements)
0
2
0
Order By: Relevance
“…Several studies have showed that BCSCs show higher levels of SOD2 compared to the non-BCSC population. This high expression strongly correlates with their aggressiveness, including stemness and metastasis (Srivastava et al, 2023;Wanandi et al, 2019). However, specific sequence variation in human SOD2 contributing to the aggressive properties remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have showed that BCSCs show higher levels of SOD2 compared to the non-BCSC population. This high expression strongly correlates with their aggressiveness, including stemness and metastasis (Srivastava et al, 2023;Wanandi et al, 2019). However, specific sequence variation in human SOD2 contributing to the aggressive properties remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, hypoxia commonly happens in rapidly growing tumors that outsource the available blood supply, resulting in hypoxia within the TME. Hypoxia induces expresses the Angiogenic Growth Factors, which are associated with the stabilization and activation of hypoxia-inducible factors (HIFs) which are transcription factors that regulate the expression of genes involved in various aspects of tumor progression, including immunosuppression [19]. It can also promote the recruitment and expansion of myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs), both of which contribute to the immunosuppression [20].…”
Section: Tumor-induced Hypoxiamentioning
confidence: 99%
“…Although these genomic studies have led to the rationale for ongoing clinical trials involving androgen receptor and PARP inhibitors in biomarker-selected populations, very few options currently exist for targeted therapy in TNBC. Moreover, several studies have demonstrated that hypoxia also induces genomic alterations in TNBC patients and is responsible for treatment resistance and recurrence [8][9][10][11]. Thus, there is a need for an improved understanding of actionable molecular alterations and their correlation with functional changes predicting drug response.…”
Section: Introductionmentioning
confidence: 99%